2016
DOI: 10.1038/ng.3706
|View full text |Cite
|
Sign up to set email alerts
|

Wheat Fhb1 encodes a chimeric lectin with agglutinin domains and a pore-forming toxin-like domain conferring resistance to Fusarium head blight

Abstract: Fusarium head blight (FHB), caused by Fusarium graminearum, is a devastating disease of wheat and barley that leads to reduced yield and mycotoxin contamination of grain, making it unfit for human consumption. FHB is a global problem, with outbreaks in the United States, Canada, Europe, Asia and South America. In the United States alone, total direct and secondary economic losses from 1993 to 2001 owing to FHB were estimated at $7.67 billion. Fhb1 is the most consistently reported quantitative trait locus (QTL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
228
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 286 publications
(245 citation statements)
references
References 36 publications
5
228
1
Order By: Relevance
“…Notably, the Rht-D1b allele had a more significant effect on anther retention and FHB severity than the Rht-B1b allele suggesting that differences in disease severity associated with the two semi-dwarfing alleles can be partly explained by their different effect on anther extrusion. A partly common genetic control of anther extrusion and plant First FHB resistance QTL is cloned (Rawat et al 2016) Initial utilization of molecular markers for selection (Del Blanco et al 2003;Yang et al 2003;Zhou et al 2003) Phenotypic selection is the only option 1999 First FHB resistance QTL are mapped (Waldron et al 1999;Bai et al 1999) Applicability of genomic selection is demonstrated (Rutkoski et al 2012) 2003 2012 2016…”
Section: Morphological and Phenological Traitsmentioning
confidence: 99%
“…Notably, the Rht-D1b allele had a more significant effect on anther retention and FHB severity than the Rht-B1b allele suggesting that differences in disease severity associated with the two semi-dwarfing alleles can be partly explained by their different effect on anther extrusion. A partly common genetic control of anther extrusion and plant First FHB resistance QTL is cloned (Rawat et al 2016) Initial utilization of molecular markers for selection (Del Blanco et al 2003;Yang et al 2003;Zhou et al 2003) Phenotypic selection is the only option 1999 First FHB resistance QTL are mapped (Waldron et al 1999;Bai et al 1999) Applicability of genomic selection is demonstrated (Rutkoski et al 2012) 2003 2012 2016…”
Section: Morphological and Phenological Traitsmentioning
confidence: 99%
“…Although a reference genome sequence can serve as a 'guide' to narrow down the location of a gene, the gene causing the phenotype of interest is often absent from the reference cultivar 1,4 which means that sequence information from a line that carries the gene of interest is needed. Repeated rounds of bacterial artificial chromosome (BAC) library screening, or chromosome walking, are usually necessary to cover the region of interest with a contiguous sequence 8 .…”
mentioning
confidence: 99%
“…Previous studies showed that Sumai3 and Wangshuibai carried the well-known major resistance QTL Fhb1 with the strongest FHB resistance (Cuthbert et al 2006;Rawat et al 2016). Since the use of Sumai3 in breeding is still unsuccessful (Chen et al 2012), breeders appreciate other germplasm of resistance with some improved and important traits.…”
Section: Discussionmentioning
confidence: 99%